2020
DOI: 10.1089/ct.2020;32.529-533
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Thyroid Disease Care

Abstract: Background Recent protests over police brutality as well as the COVID-19 pandemic have brought to light the systemic racism that pervades all sectors of our society, including the practice of medicine (1,2). Not unexpectedly, racial inequity is found in many areas of endocrinology (3), most notably in diabetes. A PubMed search, completed on October 2, 2020, of "racial disparities in diabetes" found over 1000 papers on this subject published since 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…While untreated hypothyroidism has become increasingly less common, there is evidence that untreated hypothyroidism remains more likely for certain patient groups, in particular for men, individuals younger than 45 years of age, and those without access to regular health care ( 93 , 94 ). Several studies have examined racial/ethnic factors that influence whether a patient will receive treatment for hypothyroidism ( 95 99 ). An analysis of the Cardiovascular Health Study dataset of those aged 65 years and older demonstrated that White women over any other race and sex group were more likely to start treatment with thyroid hormone ( 96 ).…”
Section: Sociodemographic Disparities In Clinical Outcomesmentioning
confidence: 99%
“…While untreated hypothyroidism has become increasingly less common, there is evidence that untreated hypothyroidism remains more likely for certain patient groups, in particular for men, individuals younger than 45 years of age, and those without access to regular health care ( 93 , 94 ). Several studies have examined racial/ethnic factors that influence whether a patient will receive treatment for hypothyroidism ( 95 99 ). An analysis of the Cardiovascular Health Study dataset of those aged 65 years and older demonstrated that White women over any other race and sex group were more likely to start treatment with thyroid hormone ( 96 ).…”
Section: Sociodemographic Disparities In Clinical Outcomesmentioning
confidence: 99%